Soccer vs. running training effects in young adult men: which programme is more effective in improvement of body composition? Randomized controlled trial - Milanović, Z; Pantelić, S; Kostić, R; Trajković, N; Sporiš, G (Biology of Sport, 2015)
The aims of this study were: 1) To determine the effects of a 12-week recreational soccer training programme and continuous endurance running on body composition of young adult men and 2) to determine which of these two programmes was more effective concerning body composition. Sixty-four participants completed the randomized controlled trial and were randomly assigned to one of three groups: a soccer training group (SOC; n=20), a running group (RUN; n=21) or a control group performing no physical training (CON; n=23). Training programmes for SOC and RUN lasted 12-week with 3 training sessions per week. Soccer sessions consisted of 60 min ordinary five-a-side, six-a-side or seven-a-side matches on a 30-45 m wide and 45-60 m long plastic grass pitch. Running sessions consisted of 60 min of continuous moderate intensity running at the same average heart rate as in SOC (~80% HRmax). All participants, regardless of group assignment, were tested for each of the following dependent variables: body weight, body height, body mass index, percent body fat, body fat mass, fat-free mass and total body water. In the SOC and RUN groups there was a significant decrease (p<0.05) in body composition parameters from pre- to post-training values for all measures with the exception of fat-free mass and total body water. Body mass index, percent body fat and body fat mass did not differ between groups at baseline, but by week 12 were significantly lower (p<0.05) in the SOC and RUN groups compared to CON. To conclude, recreational soccer training provides at least the same changes in body composition parameters as continuous running in young adult men when the training intensity is well matched.